2005
DOI: 10.1889/1.2036510
|View full text |Cite
|
Sign up to set email alerts
|

P-80: A New Oxide/Oxysulfide Based Phosphor Triad and High-Efficiency Green-Emitting (Y,Gd)[sub 2]O[sub 2]S:Tb Phosphor for FED Applications

Abstract: An oxide/oxysulfide based phosphor triad with particle sizes of around 1micrometer (green Y 2 SiO 5 :Tb or Y 2 O 2 S:Tb, and blue Y 2 SiO 5 :Ce) down to 250nm for the red Y 2 O 3 :Eu is reported. These phosphors perform well in brightness under the conditions necessary for use in FED's and are of suitable size for use in high definition screens. We also report a green emitting Y 2 O 2 S:Tb phosphor that has been prepared by a new method involving homogeneous precipitation of the precursors and a new firing reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The Tb 3+ ‐activated Gd 2 O 2 S phosphor particles were synthesized through a two‐step method: the first step was the preparation of Tb 3+ ‐doped gadolinium hydroxycarbonate precursor (Gd (OH)CO 3 :Tb 3+ ) via a urea‐based hydrothermal homogeneous precipitation method with minor modifications . The second step was the sulfuration of the Gd (OH)CO 3 :Tb 3+ .…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tb 3+ ‐activated Gd 2 O 2 S phosphor particles were synthesized through a two‐step method: the first step was the preparation of Tb 3+ ‐doped gadolinium hydroxycarbonate precursor (Gd (OH)CO 3 :Tb 3+ ) via a urea‐based hydrothermal homogeneous precipitation method with minor modifications . The second step was the sulfuration of the Gd (OH)CO 3 :Tb 3+ .…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The higher detection efficiency of the smaller Gd 2 O 2 S:Pr 3+ particles was becuase of their ability to form a thin close‐packed layer with very few “pinholes,” thereby capturing more X‐rays . In the present work, submicron‐sized Gd 2 O 2 S:Tb 3+ phosphor precursor powders were prepared by a urea hydrothermal homogeneous‐precipitation method . In addition, to encapsulate the phosphor particles on the textured surface of monocrystalline silicon (mono‐Si) solar cell, ethylene vinyl acetate (EVA), with excellent optical properties, good thermal stability, and strong adhesion, was selected as the matrix and binder .…”
Section: Introductionmentioning
confidence: 99%
“…Nanometre sized (Y 1Àx Gd x ) 2 O 2 S:Tb 3+ phosphor particles (x values in the range 0 to 1 with 0.1 increments) with activator concentrations of 0.1 and 2 mol% were synthesized using a procedure based on the urea homogenous precipitation method that we have previously described 3,4,10,13 and subsequent calcination at 900 C. The 2 mol% Tb 3+ sample series was also re-red at 1100 C. The following chemicals were used in this study: yttrium oxide and terbium oxide (99.99%, Neomaterials, UK) and gadolinium oxide (99.99%, Ampere Industrie, France); nitric acid (AnalaR, Fisher Scientic, UK), urea (99.9%, Fisher Scientic, UK), sulfur (99.5%, Sigma Aldrich, UK) and sodium carbonate (98%, Alfa Aesar, UK). All chemicals supplied were used without further purication.…”
Section: Sample Preparationmentioning
confidence: 99%
“…12 Gd 2 O 2 S:Tb 3+ and Y 2 O 2 S:Tb 3+ have also been investigated for use in eld emission displays (FED) where Y 2 O 2 S:Tb 3+ was suggested to be a promising phosphor as the green component. 13 It has been reported that the composition of the lanthanidebased oxysulde host lattice and the concentration of the Tb 3+ dopant cations have a signicant inuence on the emission colour that can range from blue to green. [3][4][5][6] The fact that tuning the composition of the phosphors controls the emission wavelength offers interesting opportunities for these phosphors in a range of novel applications as well as for improvements in current applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, fluorides have less favorable chemical, thermal and mechanical properties compared to oxides, and thus are hard to be prepared and handled [5]. Similarly, many efficient sulfide-based compounds have been explored as low-voltage phosphors, such as Y 2 O 2 S: Eu [6], Gd 2 O 2 S: Tb [7], SrGa 2 S 4 : Eu [8], etc. However, sulfide-based materials have many disadvantages, such as chemical instability, corrosion of the emitter cathode, and luminance saturation [9].…”
Section: Introductionmentioning
confidence: 99%